Analiza načrtovanih prostorskih posegov v obalnem pasu Slovenije z vidika preobrazbe obstoječega stanja - Čok, Gregor (Annales. Series historia et sociologia, 2021)
The Northern Adriatic region is facing a variety of interests, which are formally reconciled in various planning processes. A Maritime Spatial Plan is being drafted for the Slovenian sea and coastline at the national level and a new generation of spatial documents at the local level. In this context, the interests of conservation, sustainable natural resources management, and dilemmas related to business and public interests have been placed at the forefront. At the implementation level, investment incentives for spatial developments aiming to provide for an adequate infrastructure to carry out a specific activity are of key concern. Using a descriptive method, we first analysed the existing spatial conditions (developed and undeveloped land) and prepared an overview of the existing professional approaches in coastal zone management. In the second phase we recorded the current investment incentives across the entire Slovenian coast and analysed in detail the situation in the Municipality of Izola. Using a comparative method we determined that in most cases these initiatives originate from the fields of tourism and recreation. In the spatial sense, municipalities make up 58% of the entire coastline, which means that their potential implementation would significantly change the existing spatial situation. This finding opens up questions on coordination of all potential activities related to the marine environment and on the general public interest goals. The methodology of preparing spatial documents, originating from international commitments on integrated coastal zone management, provides an appropriate opportunity to make well-considered decisions and work towards a legitimate vision of development in this area.
Keywords: coastal zone; javni interes; land developments; obalna področja; planning process; prostorski razvoj; prostorsko planiranje; public interest; Slovensko Primorje; spatial form